Pengaruh Rasio Keuangan Terhadap Nilai Perusahaan - Nugroho, Kukuh Wahyu; Supriyadi, Didit; Chaerudin, Chaerudin (Gorontalo Accounting Journal, 2023)
This study aims to determine the influence of Financial Statement Ratios, which consist of Profitability Ratios (Return On Assets), Solvability Ratios (Debt to Equity Ratio) and Liquidity Ratios (Current Ratio) to Firm Value (Price to Book Value), both in partially or simultaneously terms, in consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange for the period 2017 - 2020. The study was conducted on financial ratio data, with the independent variables are Return On Assets (ROA), Debt to Equity Ratio (DER) and Current Ratio (CR) and also the dependent variable is Price to Book Value (PBV), which is obtained from audited financial statements for the period 2017 - 2020. The analytical method that the researcher uses is multiple linear analysis by carrying out several tests, such as the classical assumption test, T test and F test. The result indicates that Profitability Ratios (ROA), Solvability Ratios (DER) and Liquidity Ratios (CR) have significant effect on Firm Value (PBV), either partially or simultaneously.